M icroRNA-27a gene polymorphism (rs895819) association with risk of pulmonary tuberculosis (PTB): A case–control study - Alireza Arabshahi; Mahboobeh Sabeti Akbar-Abad; Ebrahim Alijani; Mahdi Majidpour; Sepehr Ghasemi; Zahra Mohammadghasemipour; Shahriyar Nikuei; Razieh Akhtar; Hossein Shahriari (Egyptian Journal of Medical Human Genetics)
Abstract Background Pulmonary tuberculosis (PTB), caused by the bacteria Mycobacterium tuberculosis (M.tb), remains a significant global health challenge. Research suggests that genetic factors, particularly single-nucleotide polymorphisms (SNPs) in microRNA (miRNA) genes, may influence an individual’s susceptibility to PTB. Our analysis identified a significant correlation between the rs895819 polymorphism and an elevated risk of developing PTB. Methods and materials We designed case–control research with 60 PTB patients and 60 healthy controls matched for age and sex. We used PCR–RFLP analysis to identify the differences between the samples. We used odds ratios and multivariate logistic regression. We used it in the study to make sure that it had a good mix of healthy people who were free of active tuberculosis based on clinical testing and chest X-rays and people who had been diagnosed with PTB based on clinical and radiological findings. Results Significant results were seen in the codominant 2 model (p = 0.004), the dominant model (p = 0.013), the recessive model (p = 0.008), and the allelic models (p = 0.001), with respective risk increases for PTB of 5.15, 2.62, 4.21, and 2.71 times. Conclusions We found a strong link between the miR-27a gene polymorphism (rs895819) and a higher risk of PTB. This link shows how important genetic factors are in determining the risk of getting PTB and how genetic screening could be used in public health programs to find people who are at risk. Researchers should look into how miR-27a affects the immune system’s response to tuberculosis in the future and think about what this means for therapeutic interventions.